Estimulação elétrica nervosa transcutânea em mulheres com dismenorreia primária: estudo clínico randomizado com avaliação econômica - Rodrigues, Jessica Cordeiro (Universidade Federal de São Carlos, 2024)
Introduction: Primary dysmenorrhea (PD) is a gynecological disorder characterized by pain in the abdominal or pelvic region before or during menstruation in the absence of any pelvic disease. Although Transcutaneous Electrical Nerve Stimulation (TENS) is used to relieve pain associated with PD, its cost-effectiveness and cost-utility remain poorly understood. Objective: This study aimed to evaluate TENS can be effective in treating PD symptoms and determine the cost-effectiveness associated with TENS in treating PD symptoms. Materials and methods: This study included 174 women between 18 and 45 years, with menstrual pain ≥ 4 points on the Numerical Pain Scale (END), randomized (1:1:1) by draw into 3 groups of treatment, with 58 participants in each group: aTENS (intervention group), pTENS (placebo group) and educational booklet group. The protocol consisted of 3 sessions, held once a month, for 30 minutes. In the intervention and placebo groups, a frequency of 100Hz and a pulse duration of 200μs were applied. However, in the placebo group, the current was only delivered during the first 30 seconds. Participants in the educational booklet group received guidance on health promotion and education actions related to PD. Outcomes were assessed by END, Generic six-dimensional short form quality of life questionnaire (SF-6D) and Economic Assessment Form. Assessments occurred at 2 moments: before treatment and after the 3rd month of follow-up. Statistical analysis: Two-way ANOVA was used to compare the intensity of dysmenorrhea pain due to END between the groups in the first, second and third evaluation after the protocol. For the cost-utility analysis, the QALY obtained during treatment was used. Cost-effectiveness measures were estimated in Brazilian currency (R$), while outcomes were indicated by the clinical event "pain". A significance level of 5% was adopted. Statistical analyzes were performed using the SPSS 22.0 program. Results: TENS demonstrated to be more effective than placebo TENS and educational booklet in improving clinical results over 3 months of treatment. Furthermore, TENS presented an incremental cost-effectiveness of R$0.43/no occurrence of pain. Additionally, it was estimated that each 0.01 QALY increase with TENS has a cost of R$22.25. Conclusion: TENS is a cost-effective treatment option that can be used by policymakers to improve PD care in public and private healthcare systems.
Transcutaneous electrical nerve stimulation for women with primary dysmenorrhea: a randomized controlled clinical trial with economic evaluation
Keywords: Dismenorreia; Dysmenorrhea; Saúde da mulher; Women's health; Análise de custo-efetividade; Cost-effectiveness analysis; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL